Pengaruh Kualitas Pelayanan Terhadap Kepuasan Wisatawan Di Kawasan Wisata Bahari Terpadu Mandeh - Mihardi Sanjaya Sukma Sari; Lidya Martha (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The poupose of this study is to determine the service quality effects consisting of responsiveness, empathy, tangible, assurance, and reliability on tourist satisfaction in the Mandeh tourism area, Pesisir Selatan Regency, West Sumatra Province. A total of 100 visitors were assigned as respondents (samples) of the study. The data was collected accidentally on randomly selected people as respondents. In conducting data analysis, SPSS software is used to test hypotheses. A total of five hypotheses were formulated in this study. In conclusion, this study proves that responsiveness, tangible, assurance, and reliability have a positive and significant effect on tourist satisfaction at Mandeh tourism area. While empathy does not have a positive and significant effect on tourist satisfaction at Mandeh tourism area.